Developing Quantitative Nondestructive Characterization of Nanomaterials: A Case Study on Sequential Infiltration Synthesis of Block Copolymers - Cara, Eleonora; Hönicke, Philipp; Kayser, Yves; Lindner, Jörg K. N.; Castellino, Micaela; Murataj, Irdi; Porro, Samuele; Angelini, Angelo; De Leo, Natascia; Pirri, Candido Fabrizio; Beckhoff, Burkhard; Boarino, Luca; et al. (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Feasibility Study of Compression Molding for Large Reinforcement Structures in the Commercial Vehicle Sector - Lückenkötter, Julian; Leimbach, J.P.; Stallmeister, Tim; Marten, Thorsten; Tröster, Thomas (Materials Research Proceedings)
Abstract. Due to an increasing volume of shipments, there is a significant need for more delivery vehicles. One approach to reduce the associated increase in carbon dioxide (CO2) emissions is a new light weight design approach involving the substitution of conventional materials with glass fiber mat-reinforced thermoplastics (GMT) based on polypropylene (PP). The application of GMT by compression molding is a widely used process in the automotive industry. However, application in the commercial vehicle sector requires much larger dimensions, making it necessary to clarify whether the manufacturing process and material are suitable for semi-structural applications on this scale. To find this out, two replacement geometries are abstracted in this study and manufactured by varying the main manufacturing parameters. The feasibility can be demonstrated by recording and analyzing the resulting process variables and measuring the formed fiber distribution. At the end of the paper, recommendations are given for the production of GMT structures on the scale of commercial vehicles.
Keywords: Compression Molding; Fiber Content; Process Development; Lightweight Design

Selective Discrimination between CO and H2 with Copper–Ceria-Resistive Gas Sensors - Baier, Dominik; Priamushko, Tatiana; Weinberger, Christian; Kleitz, Freddy; Tiemann, Michael (ACS Sensors)
The production of hydrogen and the utilization of biomass for sustainable concepts of energy conversion and storage require gas sensors that discriminate between hydrogen (H2) and carbon monoxide (CO). Mesoporous copper–ceria (Cu–CeO2) materials with large specific surface areas and uniform porosity are prepared by nanocasting, and their textural properties are characterized by N2 physisorption, powder XRD, scanning electron microscopy, transmission electron microscopy, and energy-dispersive X-ray spectroscopy. The oxidation states of copper (Cu+, Cu2+) and cerium (Ce3+, Ce4+) are investigated by XPS. The materials are used as resistive gas sensors for H2 and CO. The sensors show a stronger response to CO than to H2 and low cross-sensitivity to humidity. Copper turns out to be a necessary component; copper-free ceria materials prepared by the same method show only poor sensing performance. By measuring both gases (CO and H2) simultaneously, it is shown that this behavior can be utilized for selective sensing of CO in the presence of H2.
Keywords: Fluid Flow and Transfer Processes; Process Chemistry and Technology; Instrumentation; Bioengineering

More Isn’t Always Better – Measuring Customers’ Preferences for Digital Process Transparency - Brennig, Katharina; Müller, Oliver (Hawaii International Conference on System Sciences)
Digital technologies have made the line of visibility more transparent, enabling customers to get deeper insights into an organization’s core operations than ever before. This creates new challenges for organizations trying to consistently deliver high-quality customer experiences. In this paper we conduct an empirical analysis of customers’ preferences and their willingness-to-pay for different degrees of process transparency, using the example of digitally-enabled business-to-customer delivery services. Applying conjoint analysis, we quantify customers’ preferences and willingness-to-pay for different service attributes and levels. Our contributions are two-fold: For research, we provide empirical measurements of customers’ preferences and their willingness-to-pay for process transparency, suggesting that more is not always better. Additionally, we provide a blueprint of how conjoint analysis can be applied to study design decisions regarding changing an organization’s digital line of visibility. For practice, our findings enable service managers to make decisions about process transparency and establishing different levels of service quality.
Keywords: Digital Services; Line of Visibility; Process Transparency; Customer Preferences; Conjoint Analysis

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Proactive Management of Requirement Changes in the Development of Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Preuß, Daniel (Applied Sciences)
Requirement changes and cascading effects of change propagation are major sources of inefficiencies in product development and increase the risk of project failure. Proactive change management of requirement changes yields the potential to handle such changes efficiently. A systematic approach is required for proactive change management to assess and reduce the risk of a requirement change with appropriate effort in industrial application. Within the paper at hand, a novel method for Proactive Management of Requirement Changes (ProMaRC) is presented. It is developed in close collaboration with industry experts and evaluated based on workshops, pilot users’ feedback, three industrial case studies from the automotive industry and five development projects from research. To limit the application effort, an automated approach for dependency analysis based on the machine learning technique BERT and semi-automated assessment of change likelihood and impact using a modified PageRank algorithm is developed. Applying the method, the risks of requirement changes are assessed systematically and reduced by means of proactive change measures. Evaluation shows high performance of dependency analysis and confirms the applicability and usefulness of the method. This contribution opens up the research space of proactive risk management for requirement changes which is currently almost unexploited. It enables more efficient product development.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Powder Spread Flaws in Polymer Laser Sintering and its Influences on Mechanical Performance - Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 33nd Annual International Solid Freeform Fabrication Symposium)
By monitoring the recoating process within polymer laser sintering production, it was shown that multiple powder-spread-flaws can be detected. Those groove-like flaws are expected to be the result of agglomerates jamming between the recoater and the last powder layer. This work is analyzing the interaction between powder-spread-flaws and part properties, showing the influence of the recoating process on the performance of laser sintering parts. Therefore, artificial powder-spread-flaws are applied to the build jobs of tensile test specimens which are measured and analyzed regarding the elongation at break, strength and fracture position. For the characteristics of the flaws, the artificial grooves are varied in depth and width. Furthermore, the position of the flaw is changed form mid part to close to surface areas. It was shown, that several flaws are visible at the part surface, resulting in stress concentration and reduced performance. But there are as well parts with flaw-layers, which are not visible after the build process on the part. Those parts can have significantly reduced mechanical properties as well.
Keywords: Selective Sasersintering; Process Monitoring; Powder Spread

Towards a Process Model for Social Media Marketing - Arslan, Kader; Trier, Matthias (Proceedings of the 33rd Australasian Conference on Information Systems (ACIS 2022))
Keywords: Social media; Social media marketing process; Social media strategy; Social media management; Guidelines

A Techno-Economic Assessment of Fischer–Tropsch Fuels Based on Syngas from Co-Electrolysis - Peters, Ralf; Wegener, Nils; Samsun, Remzi Can; Schorn, Felix; Riese, Julia; Grünewald, Marcus; Stolten, Detlef (Processes)
As a part of the worldwide efforts to substantially reduce CO2 emissions, power-to-fuel technologies offer a promising path to make the transport sector CO2-free, complementing the electrification of vehicles. This study focused on the coupling of Fischer–Tropsch synthesis for the production of synthetic diesel and kerosene with a high-temperature electrolysis unit. For this purpose, a process model was set up consisting of several modules including a high-temperature co-electrolyzer and a steam electrolyzer, both of which were based on solid oxide electrolysis cell technology, Fischer–Tropsch synthesis, a hydrocracker, and a carrier steam distillation. The integration of the fuel synthesis reduced the electrical energy demand of the co-electrolysis process by more than 20%. The results from the process simulations indicated a power-to-fuel efficiency that varied between 46% and 67%, with a decisive share of the energy consumption of the co-electrolysis process within the energy balance. Moreover, the utilization of excess heat can substantially to completely cover the energy demand for CO2 separation. The economic analysis suggests production costs of 1.85 €/lDE for the base case and the potential to cut the costs to 0.94 €/lDE in the best case scenario. These results underline the huge potential of the developed power-to-fuel technology.
Keywords: Process Chemistry and Technology; Chemical Engineering (miscellaneous); Bioengineering

Exogenous Shocks and Business Process Management - Röglinger, Maximilian; Plattfaut, Ralf; Borghoff, Vincent; Kerpedzhiev, Georgi; Becker, Jörg; Beverungen, Daniel; vom Brocke, Jan; Van Looy, Amy; del-Río-Ortega, Adela; Rinderle-Ma, Stefanie; Rosemann, Michael; Santoro, Flavia Maria; et al. (Business & Information Systems Engineering)
Abstract Business process management (BPM) drives corporate success through effective and efficient processes. In recent decades, knowledge has been accumulated regarding the identification, discovery, analysis, design, implementation, and monitoring of business processes. This includes methods and tools for tackling various kinds of process change such as continuous process improvement, process reengineering, process innovation, and process drift. However, exogenous shocks, which lead to unintentional and radical process change, have been neglected in BPM research although they severely affect an organization’s context, strategy, and business processes. This research note conceptualizes the interplay of exogenous shocks and BPM in terms of the effects that such shocks can have on organizations’ overall process performance over time. On this foundation, related challenges and opportunities for BPM via several rounds of idea generation and consolidation within a diverse team of BPM scholars are identified. The paper discusses findings in light of extant literature from BPM and related disciplines, as well as present avenues for future (BPM) research to invigorate the academic discourse on the topic.
Keywords: Information Systems; Business process management; Exogenous shocks; Challenges; Opportunities

Insolvcency Process in Germany and the insol database: A research Note - Ahlers, Theresa; Edossa, Fikir Worku; Uckert, Matthias; Kosi, Urska
This research note links the legal framework of the insolvency process of German firms to the information available in the newly-constructed insol database. In particular, the database contains information from documents published by German insolvency courts in period 2005- 2022. This research note first presents the insolvency process with steps and events of the process as determined by the Insolvency Law (InsO). Next, it classifies the documents to specific steps and events, and then presents their information content using textual analysis. Specifically, we identify target phrases via manual document checks and then create regular expressions for the target phrases. Classification of documents allows us to sketch most common paths that insolvent firms go through.
Keywords: insol database; insolvency process; Germany; court fillings

The influence of manufacturing processes and optical measurement methods on the damage behavior of HX340LAD micro-alloyed steels - Otroshi, Mortaza; Meschut, Gerson; Nesakumar, Aathavan (Journal of Manufacturing Engineering)
This study deals with the damage behavior of metallic materials by the application of different manufacturing processes and using different optical measurement methods to identify the crack initiation in the damage specimen. The study is intended to highlight the importance of considering manufacturing processes and optical measurement methods in a numerical simulation when analyzing the damage behavior of metallic materials. To describe the damage behavior of the material in the process chain simulations, it is important to calibrate the parameters of damage model more accurately. These parameters are determined using experimental investigation of desired damage specimens. In this regard, a selected damage specimen manufactured by different cutting processes is first experimentally and then numerically investigated. It is shown that the manufacturing process and the optical measurement methods influence the stress state analyzed in the numerical simulation.
Keywords: Damage behaviour; Stress triaxiality; Manufacturing process and Optical measurement

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; López-Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Sustainable oxidation catalysis supported by light: Fe-poly (heptazine imide) as a heterogeneous single-atom photocatalyst - da Silva, Marcos A.R.; Silva, Ingrid F.; Xue, Qi; Lo, Benedict T.W.; Tarakina, Nadezda V.; Nunes, Barbara N.; Adler, Peter; Sahoo, Sudhir K.; Bahnemann, Detlef W.; Lopez Salas, Nieves; Savateev, Aleksandr; Ribeiro, Caue; et al. (Applied Catalysis B: Environmental)
Keywords: Process Chemistry and Technology; General Environmental Science; Catalysis

Forming of metastable austenitic stainless steel tubes with axially graded martensite content by flow-forming - Arian, Bahman; Homberg, Werner; Riepold, Markus; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank
One of the main objectives of production engineering is to reproducibly manufacture (complex) defect-free parts. To achieve this, it is necessary to employ an appropriate process or tool design. While this will generally prove successful, it cannot, however, offset stochastic defects with local variations in material properties. Closed-loop process control represents a promising approach for a solution in this context. The state of the art involves using this approach to control geometric parameters such as a length. So far, no research or applications have been conducted with closed-loop control for microstructure and product properties. In the project on which this paper is based, the local martensite content of parts is to be adjusted in a highly precise and reproducible manner. The forming process employed is a special, property-controlled flow-forming process. A model-based controller is thus to generate corresponding correction values for the tool-path geometry and tool-path velocity on the basis of online martensite content measurements. For the controller model, it is planned to use a special process or microstructure (correlation) model. The planned paper not only describes the experimental setup but also presents results of initial experimental investigations for subsequent use in the closed-loop control of α’-martensite content during flow-forming.
Keywords: Flow-forming; Spinning; Process Strategy; Martensite Content; Property Control; Micromagnetic Measurement; Metastable Austenitic Stainless Steel

A composite consisting of intermetallic Ni3Fe and nitrogen-doped carbon for electrocatalytic water oxidation: The effect of increased pyridinic nitrogen dopant - Liu, Dan; Zhai, Haichao; Hu, Jie; Pan, Ying; Xu, Gengsheng; Zhu, Chuhong; Yuan, Yupeng (Ceramics International)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Process Chemistry and Technology; Ceramics and Composites; Electronic; Optical and Magnetic Materials

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Explanation as a Social Practice: Toward a Conceptual Framework for the Social Design of AI Systems - Rohlfing, Katharina J.; Cimiano, Philipp; Scharlau, Ingrid; Matzner, Tobias; Buhl, Heike M.; Buschmeier, Hendrik; Esposito, Elena; Grimminger, Angela; Hammer, Barbara; Haeb-Umbach, Reinhold; Horwath, Ilona; Hüllermeier, Eyke; et al. (IEEE Transactions on Cognitive and Developmental Systems)
One objective of current research in explainable intelligent systems is to implement social aspects in order to increase the relevance of explanations. In this paper, we argue that a novel conceptual framework is needed to overcome shortcomings of existing AI systems with little attention to processes of interaction and learning. Drawing from research in interaction and development, we first outline the novel conceptual framework that pushes the design of AI systems toward true interactivity with an emphasis on the role of the partner and social relevance. We propose that AI systems will be able to provide a meaningful and relevant explanation only if the process of explaining is extended to active contribution of both partners that brings about dynamics that is modulated by different levels of analysis. Accordingly, our conceptual framework comprises monitoring and scaffolding as key concepts and claims that the process of explaining is not only modulated by the interaction between explainee and explainer but is embedded into a larger social context in which conventionalized and routinized behaviors are established. We discuss our conceptual framework in relation to the established objectives of transparency and autonomy that are raised for the design of explainable AI systems currently.
Keywords: Explainability; process ofexplaining andunderstanding; explainable artificial systems

Far-field prediction combining simulations with near-field measurements for EMI assessment of PCBs - Schröder, Dominik; Lange, Sven; Hangmann, Christian; Hedayat, Christian (Tensorial Analysis of Networks (TAN) Modelling for PCB Signal Integrity and EMC Analysis)
Using near-field (NF) scan data to predict the far-field (FF) behaviour of radiating electronic systems represents a novel method to accompany the whole RF design process. This approach involves so-called Huygens' box as an efficient radiation model inside an electromagnetic (EM) simulation tool and then transforms the scanned NF measured data into the FF. For this, the basic idea of the Huygens'box principle and the NF-to-FF transformation are briefly presented. The NF is measured on the Huygens' box around a device under test using anNF scanner, recording the magnitude and phase of the site-related magnetic and electric components. A comparison between a fullwave simulation and the measurement results shows a good similarity in both the NF and the simulated and transformed FF.Thus, this method is applicable to predict the FF behaviour of any electronic system by measuring the NF. With this knowledge, the RF design can be improved due to allowing a significant reduction of EM compatibility failure at the end of the development flow. In addition, the very efficient FF radiation model can be used for detailed investigations in various environments and the impact of such an equivalent radiation source on other electronic systems can be assessed.
Keywords: Huygens' box; NF-to-FF transformation; efficient FF radiation model; FF behaviour; EMI assessment; PCB; near-field measurements; efficient radiation model; far-field behaviour; RF design process; far-field prediction; Huygens'box principle; fullwave simulation; electronic system radiation; equivalent radiation source; electromagnetic simulation tool; near-field scan data; EM compatibility failure reduction

Numerical analysis of the robustness of clinching process considering the pre-forming of the parts - Bielak, Christian Roman; Böhnke, Max; Beck, Robert; Bobbert, Mathias; Meschut, Gerson (Journal of Advanced Joining Processes.)
Keywords: Clinching; process simulation; FEM; pre-straining; sensitivity analysis

The Deterioration Mechanism of Silicone Molds in Polyurethane Vacuum Casting - Wortmann, Martin; Frese, Natalie; Keil, Waldemar; Brikmann, Johannes; Biedinger, Jan; Brockhagen, Bennet; Reiss, Günter; Schmidt, Claudia; Gölzhäuser, Armin; Moritzer, Elmar; Hüsgen, Bruno (ACS Applied Polymer Materials)
Keywords: Organic Chemistry; Polymers and Plastics; Process Chemistry and Technology

Transformable Decentral Production for Local Economies with Minimized Carbon Footprint - Pannok, Maik; Finkbeiner, Marco; Fasel, Henrik; Riese, Julia; Lier, Stefan (ChemBioEng Reviews)
Abstract Due to high energy‐intensive processes and a dependence on carbon‐based materials, the process industry plays a major role in climate change. Therefore, the substitution of fossil resources by bio‐based resources is indispensable. This leads to challenges arising from accompanying changes of the type, amount and location of resources. At the same time, transformable production systems are currently in the focus of research addressing the required flexibility. These systems which consist of modular production and logistics units offer the possibility to adapt flexibly in volatile conditions within dynamic supply chains. Hence, this work compiles elements for environmental sustainability, which minimize the carbon footprint in the process industry: transformable production systems, the utilization of bio‐based resources, carbon dioxide and renewable energy as well as the application of these elements in decentral production networks. Finally, possible use cases are determined based on the combination of these elements through a multi‐criteria analysis.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Seven Paradoxes of Business Process Management in a Hyper-Connected World - Beverungen, Daniel; Buijs, Joos C. A. M.; Becker, Jörg; Di Ciccio, Claudio; van der Aalst, Wil M. P.; Bartelheimer, Christian; vom Brocke, Jan; Comuzzi, Marco; Kraume, Karsten; Leopold, Henrik; Matzner, Martin; Mendling, Jan; et al. (Business & Information Systems Engineering)
Business Process Management is a boundary-spanning discipline that aligns operational capabilities and technology to design and manage business processes. The Digital Transformation has enabled human actors, information systems, and smart products to interact with each other via multiple digital channels. The emergence of this hyper-connected world greatly leverages the prospects of business processes – but also boosts their complexity to a new level. We need to discuss how the BPM discipline can find new ways for identifying, analyzing, designing, implementing, executing, and monitoring business processes. In this research note, selected transformative trends are explored and their impact on current theories and IT artifacts in the BPM discipline is discussed to stimulate transformative thinking and prospective research in this field.
Keywords: Business process management (BPM); Social computing; Smart devices; Big data analytics; Real-time computing; BPM life-cycle

Banks and Corporate Income Taxation: A Review - Gawehn, Vanessa
n this paper, I review the empirical literature in the intersection of banks and corporate income taxation that emerged over the last two decades. To structure the included studies, I use a stakeholder approach and outline how corporate income taxation plays into the relation of banks and their four main stakeholders: bank regulators, customers, investors and tax authorities. My contribution to the literature is threefold: First, I contribute by providing, to the best of my knowledge, a first comprehensive review on this topic. Second, I point to areas for future research. Third, I deduce policy implications from the studies under review. In sum, the studies show that taxes distort banks’ pricing decisions, the relative attractiveness of debt and equity financing, the decision to report on or off the balance sheet and banks’ investment allocations. Empirical insights on how tax rules affect banks’ decision-making are helpful for policymakers to tailor suitable and sustainable tax legislation directed at banks.
Keywords: corporate income taxes; banks; stakeholder approach; decision-making process

Modeling and Validating Fixed‐Bed Reactors: A State‐of‐the‐Art Review - Stegehake, Carolin; Riese, Julia; Grünewald, Marcus (ChemBioEng Reviews)
Abstract Modeling of heat and mass transfer in fixed‐bed reactors for heterogeneously catalyzed gas phase reactions is possible using different methods. Homogeneous and heterogeneous continuum models as well as particle resolved modeling of fixed‐bed reactors show high potential for application. Considering those approaches, advantages and disadvantages as well as underlying assumptions and boundary conditions are discussed. Additionally, methods for experimental validation are presented and discussed focusing on the two‐dimensional homogeneous models.
Keywords: Industrial and Manufacturing Engineering; Filtration and Separation; Process Chemistry and Technology; Biochemistry; Chemical Engineering (miscellaneous); Bioengineering

Experimental investigations on the impact of bond process parameters in two-dimensional ultrasonic copper bonding - Dymel, Collin; Schemmel, Reinhard; Hemsel, Tobias; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias ((Proceedings of 8th Electronics IEEE CPMT Symposium Japan (ICSJ 2018), Kyoto, Japan))
Ultrasonic bonding and welding are common friction based approaches in the assembly of power electronics. Interconnections with cross-sections of 0.3 mm² up to 12 mm² made from copper are well suited in high power applications. For increasing friction energy, which is responsible for bond formation, a two-dimensional vibration approach is applied to newly developed interconnection pins. Using two-dimensional vibration for bonding requires identification of suitable bonding parameters. Even though simulation models of wire bonding processes exist, parameters for the two-dimensional pin-bonding process cannot be derived accurately yet. Within this contribution, a methodology and workflow for experimental studies identifying a suitable bond parameter space are presented. The results of a pre-study are used to set up an extensive statistical parameter study, which gives insights about the bond strength change due to bond process parameter variation. By evaluation of electrical data captured during bonding, errors biasing the resulting shear forces are identified. All data obtained during the experimental study is used to build a statistical regression model suitable for predicting shear forces. The accuracy of the regression model’s predictions is determined and the applicability to predict process parameters or validate simulation models is assessed. Finally, the influence of the tool trajectory on the bond formation is determined, comparing one dimensional, elliptic and circular trajectories.
Keywords: ultrasonic two-dimensional bonding; electrical interconnection; process parameters

Intelligent Production of Wire Bonds using Multi-Objective Optimization – Insights, Opportunities and Challenges - Unger, Andreas; Hunstig, Matthias; Meyer, Tobias; Brökelmann, Michael; Sextro, Walter (In Proceedings of IMAPS 2018 – 51st Symposium on Microelectronics, Pasadena, CA, 2018)
Ultrasonic wire bonding is an indispensable process in the industrial manufacturing of semiconductor devices. Copper wire is increasingly replacing the well-established aluminium wire because of its superior electrical, thermal and mechanical properties. Copper wire processes differ significantly from aluminium processes and are more sensitive to disturbances, which reduces the range of parameter values suitable for a stable process. Disturbances can be compensated by an adaption of process parameters, but finding suitable parameters manually is difficult and time-consuming. This paper presents a physical model of the ultrasonic wire bonding process including the friction contact between tool and wire. This model yields novel insights into the process. A prototype of a multi-objective optimizing bonding machine (MOBM) is presented. It uses multi-objective optimization, based on the complete process model, to automatically select the best operating point as a compromise of concurrent objectives.
Keywords: wire bonding; multi-objective optimization; process model; copper wire; self-optimization

Innovative scaling strategies for a fast development of apparatuses by modular process engineering - Lier, Stefan; Riese, Julia; Cvetanoska, Gordana; Lesniak, Anna Katharina; Müller, Stephan; Paul, Sarah; Sengen, Laura; Grünewald, Marcus (Chemical Engineering and Processing - Process Intensification)
Keywords: Industrial and Manufacturing Engineering; Process Chemistry and Technology; Energy Engineering and Power Technology; General Chemical Engineering; General Chemistry

The Role of Gender in Business Process Management Competence Supply - Gorbacheva, Elena; Stein, Armin; Schmiedel, Theresa; Müller, Oliver (Business and Information Systems Engineering)
Keywords: BPM workforce; Business process management; Competences; Gender diversity; Latent semantic analysis; Skills; Text mining

Towards a typology of business process management professionals: identifying patterns of competences through latent semantic analysis - Müller, Oliver; Schmiedel, Theresa; Gorbacheva, Elena; vom Brocke, Jan (Enterprise Information Systems)
Keywords: abilities; business process management; competences; knowledge; latent semantic analysis; professionals; skills; typology

An Economic Theory of 'Destabilization War' - Gries, Thomas; Haake, Claus-Jochen
While Islamic State is the most present example, it is a fact that in many places around the globe, throughout history initially small groups have tried to challenge and destabilize or even overthrow governments by means of terrorist and guerrilla strategies. Therefore, we answer two questions. Why does a small group of insurgents believe it can overthrow the government by turning violent, even if the government is clearly superior? And how does a conflict develop into terrorism, a guerilla war, or a major conventional civil war, or is resolved peacefully? We develop a formal model for rebels and government and derive optimal choices. Further, we focus on three elements as important ingredients of a "destabilization war". All three of these - large random events, time preference (which we relate to ideology), and choice of duration of fight - are rarely considered in formal conflict theory. We can answer the above two questions using game theory analysis. First, insurgents rise up because they hope to destabilize through permanent challenging attacks. In this context, large randomness is an important ally of rebels. While each individual attack may have a low impact, at some point a large random event could lead to success. Hence, the duration of activities is a constitutive element of this kind of armed conflict. Patience (low time preference), which may reflect rebels' degree of ideological motivation, is crucial. Second, the mode of warfare or the conflict resolutions that develop are generally path-dependent and conditioned on the full set of options (including compromise). Various conditions (level of funding, ease of recruitment, access to weapons) influence different modes of warfare or a peaceful compromise in a complex way.
Keywords: terrorism; civil war; conflict duration; game theory; stochastic process; ideology

Reliable Manufacturing of Heavy Copper Wire Bonds Using Online Parameter Adaptation - Meyer , Tobias; Unger, Andreas; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (IEEE 66th Electronic Components and Technology Conference)
Usage of copper wire bonds allows to push power boundaries imposed by aluminum wire bonds. Copper allows higher electrical, thermal and mechanical loads than aluminum, which currently is the most commonly used material in heavy wire bonding. This is the main driving factor for increased usage of copper in high power applications such as wind turbines, locomotives or electric vehicles. At the same time, usage of copper also increases tool wear and reduces the range of parameter values for a stable process, making the process more challenging. To overcome these drawbacks, parameter adaptation at runtime using self-optimization is desired. A self-optimizing system is based on system objectives that evaluate and quantify system performance. System parameters can be changed at runtime such that pre-selected objective values are reached. For adaptation of bond process parameters, model-based self-optimization is employed. Since it is based on a model of the system, the bond process was modeled. In addition to static model parameters such as wire and substrate material properties and vibration characteristics of transducer and tool, variable model inputs are process parameters. Main simulation result is bonded area in the wiresubstrate contact. This model is then used to find valid and optimal working points before operation. The working point is composed of normal force and ultrasonic voltage trajectories, which are usually determined experimentally. Instead, multiobjective optimalization is used to compute trajectories that simultaneously optimize bond quality, process duration, tool wear and probability of tool-substrate contacts. The values of these objectives are computed using the process model. At runtime, selection among pre-determined optimal working points is sufficient to prioritize individual objectives. This way, the computationally expensive process of numerically solving a multiobjective optimal control problem and the demanding high speed bonding process are separated. To evaluate to what extent the pre-defined goals of self-optimization are met, an offthe- shelf heavy wire bonding machine was modified to allow for parameter adaptation and for transmitting of measurement data at runtime. This data is received by an external computer system and evaluated to select a new working point. Then, new process parameters are sent to the modified bonding machine for use for subsequent bonds. With these components, a full self-optimizing system has been implemented.
Keywords: Self-optimization; adaptive system; bond process; copper wire

Validated Simulation of the Ultrasonic Wire Bonding Process - Unger, Andreas; Schemmel, Reinhard; Meyer, Tobias; Eacock, Florian; Eichwald, Paul; Althoff, Simon; Sextro, Walter; Brökelmann, Michael; Hunstig, Matthias; Guth, Karsten (Wear Modeling in Copper Wire Wedge Bonding. IEEE CPMT Symposium Japan, 2016)
To increase quality and reliability of copper wire bonds, self-optimization is a promising technique. For the implementation of self-optimization for ultrasonic heavy copper wire bonding machines, a model of stick-slip motion between tool and wire and between wire and substrate during the bonding process is essential. Investigations confirm that both of these contacts do indeed show stick-slip movement in each period oscillation. In a first step, this paper shows the importance of modeling the stick-slip effect by determining, monitoring and analyzing amplitudes and phase angles of tooltip, wire and substrate experimentally during bonding via laser measurements. In a second step, the paper presents a dynamic model which has been parameterized using an iterative numerical parameter identification method. This model includes Archard’s wear approach in order to compute the lost volume of tool tip due to wear over the entire process time. A validation of the model by comparing measured and calculated amplitudes of tool tip and wire reveals high model quality. Then it is then possible to calculate the lifetime of the tool for different process parameters, i.e. values of normal force and ultrasonic voltage.
Keywords: the Ultrasonic Wire Bonding Process

Structure of Ultrahigh Molecular Weight Polyethylene-Air Counterflow Flame (Физика горения и взрыва)
Keywords: Process Chemistry and Technology; Mechanical Engineering

Improving the bond quality of copper wire bonds using a friction model approach - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (Electronic Components and Technology Conference (ECTC), 2014 IEEE 64th)
In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production. To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level where van der Waals forces are able to arise between atoms. Also, enough friction energy referred to the total contact area has to be generated to activate the surfaces. Therefore, a friction model is used to simulate the joining process. This model calculates the resulting energy of partial areas in the contact surface and provides information about the adhesion process of each area. The focus here is on the arising of micro joints in the contact area depending on the location in the contact and time. To validate the model, different touchdown forces are used to vary the initial contact areas of wire and substrate. Additionally, a piezoelectric tri-axial force sensor is built up to identify the known phases of pre-deforming, cleaning, adhering and diffusing for the real bonding process to map with the model. Test substrates as DBC and copper plate are used to show the different formations of a wedge bond connection due to hardness and reaction propensity. The experiments were done by using 500 $μ$m copper wire and a standard V-groove tool.
Keywords: adhesion; circuit reliability; deformation; diffusion; fatigue cracks; friction; interconnections; lead bonding; van der Waals forces; Cu; adhering process; adhesion process; ampacity improvement; bond quality improvement; cleaning process; diffusing process; fatigue fracture failure; friction energy; friction model; heat dissipation; mechanical strength; piezoelectric triaxial force sensor; predeforming process; size 500 mum; total contact area; van der Waals forces; wedge copper wire bonding; Bonding; Copper; Finite element analysis; Force; Friction; Substrates; Wires

Synthesis of cyclic carbonates from epoxides and CO2 catalyzed by potassium iodide and amino alcohols - Werner, Thomas; Tenhumberg, Nils (Journal of CO2 Utilization)
Keywords: Process Chemistry and Technology; Waste Management and Disposal; Chemical Engineering (miscellaneous)

Designing interaction routines in service networks: A modularity and social construction-based approach - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (Scandinavian Journal of Information Systems)
Keywords: Business process management; Conceptual modeling; Interaction routines; Modular design; Service networks; Social construction

Bridging the gap between manufacturing and service through IT-based boundary objects - Becker, Jorg; Beverungen, Daniel; Knackstedt, Ralf; Matzner, Martin; Müller, Oliver; Pöppelbuss, Jens (IEEE Transactions on Engineering Management)
Keywords: Action research; boundary spanning; business process management (BPM); service blueprinting; service networks

On the selective aerobic oxidation of benzyl alcohol with Pd/Au-nanoparticles in batch and flow - Alex, Hannes; Steinfeldt, Norbert; Jähnisch, Klaus; Bauer, Matthias; Hübner, Sandra (Nanotechnology Reviews)
Abstract Nanoparticles (NP) have specific catalytic properties, which are influenced by parameters like their size, shape, or composition. Bimetallic NPs, composed of two metal elements can show an improved catalytic activity compared to the monometallic NPs. We, herein, report on the selective aerobic oxidation of benzyl alcohol catalyzed by unsupported Pd/Au and Pd NPs at atmospheric pressure. NPs of varying compositions were synthesized and characterized by UV/Vis spectroscopy, transmission electron microscopy (TEM), and small-angle X-ray scattering (SAXS). The NPs were tested in the model reaction regarding their catalytic activity, stability, and recyclability in batch and continuous procedure. Additionally, in situ extended X-ray absorption fine structure (EXAFS) measurements were performed in order to get insight in the process during NP catalysis.
Keywords: Surfaces; Coatings and Films; Process Chemistry and Technology; Energy Engineering and Power Technology; Biomaterials; Medicine (miscellaneous); Biotechnology

Studienprogramme als didaktische Gestaltungs-und Untersuchungseinheit: Theoretische Grundlegung und empirische Analyse - Jenert, Tobias
Mit welchen Erwartungen und Anforderungen sehen sich Studierende im Hochschulalltag konfrontiert? Wie muss nach Ansicht der Studierenden gehandelt werden, um das Studium "erfolgreich" zu bewältigen? Wie laufen die Auswahl unterschiedlicher Lernaktivitäten im Studium sowie die Allokation von Ressourcen im Detail ab? Diese und weitere Fragen sind vor allem im Zusammenhang mit der Debatte um die Bologna-Reform stärker in den Mittelpunkt gerückt. Denn während modularisierte Curricula und Credit-Point-Systeme oft nach administrativ-organisatorischen Gesichtspunkten eingeführt wurden, hat die Gestaltung der Studienstrukturen auf Programmebene zwangsweise Auswirkungen auf das Studienhandeln - und damit auch auf das Lernen der Studierenden. Es gibt viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren: Die Rede ist von Verschulung, Entwissenschaftlichung und Arbeitsüberlastung und Studierende stehen im Verdacht, ihren Studienpfad eher im Sinne einer Credit-Point-Jagd denn interessengeleitet zu gestalten. In der Regel bleibt es dabei jedoch bei anekdotischen Beobachtungen - es fehlt bislang an gesicherten Erkenntnissen über Zusammenhänge zwischen Bologna-konformen Studienkontexten und dem Handeln Studierender. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Stattdessen wurde vorwiegend das Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht. Diejenigen, die Studienprogramme nach didaktischen Gesichtspunkten gestalten wollen müssen wissen, wie Studierende mit unterschiedlichen Studienstrukturen umgehen. Denn nur so ist eine planvolle Programmgestaltung im Sinne pädagogischer Zielsetzungen und didaktischer Prinzipien möglich. Die vorliegende Arbeit nimmt diese Problemstellung auf und untersucht, welche Zielvorstellungen und Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln. Im Einzelnen wird gefragt, (1) welche Vorstellungen, Wahrnehmungen und Handlungslogiken das Handeln Studierender in unterschiedlichen Studienprogrammen prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Ausgehend von diesen beiden Fragestellungen wird zunächst ein theoretisch fundierter Analyserahmen für Studienprogramme entwickelt. Darauf aufbauend werden verschiedene Studienprogramme empirisch untersucht, um schliesslich Design-Prinzipien für die Gestaltung von Studienprogrammen zu formulieren. Es wird nicht davon ausgegangen, dass Studienstrukturen das Handeln Studierender im Sinne eines kausalen Wirkungszusammenhangs bestimmen. Vielmehr wird gefragt, was die Studierenden mit den Strukturen, auf die sie treffen, machen. Studienprogramme werden als kulturelle Einheiten verstanden, innerhalb derer sich spezifische handlungsleitende Vorstellungen und Normen entwickeln. Diese impliziten Regeln des Studienhandelns - das so genannte "Hidden Curriculum" - und vor allem auch die dahinterliegenden Konstruktionsprozesse aufzudecken, ist Ziel dieser Arbeit.
Keywords: Studierverhalten; Hochschuldidaktik; Lernpsychologie; Kulturpsychologie; Bologna-Prozess; Curriculumentwicklung; Hochschulbildung; Study programme; Bologna-process; educational development; cultural psychology; higher education; curriculum development

Beyond process monitoring: A proof-of-concept of event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Business Process Management Journal)
Purpose – The purpose of this paper is to show how to employ complex event processing (CEP) for the observation and management of business processes. It proposes a conceptual architecture of BPM event producer, processor, and consumer and describes technical implications for the application with standard software in a perfect order scenario. Design/methodology/approach – The authors discuss business process analytics as the technological background. The capabilities of CEP in a BPM context are outlined an architecture design is proposed. A sophisticated proof-of-concept demonstrates its applicability. Findings – The results overcome the separation and data latency issues of process controlling, monitoring, and simulation. Distinct analyses of past, present, and future blur into a holistic real-time approach. The authors highlight the necessity for configurable event producer in BPM engines, process event support in CEP engines, a common process event format, connectors to visualizers, notifiers and return channels to the BPM engine. Research limitations/implications – Further research will thoroughly evaluate the approach in a variety of business settings. New concepts and standards for the architecture's building blocks will be needed to improve maintainability and operability. Practical implications – Managers learn how CEP can yield insights into business processes' operations. The paper illustrates a path to overcome inflexibility, latency, and missing feedback mechanisms of current process modeling and control solutions. Software vendors might be interested in the conceptualization and the described needs for further development. Originality/value – So far, there is no commercial CEP-based BPM solution which facilitates a round trip from insight to action as outlines. As major software vendors have begun developing solutions (BPM/BPA solutions), this paper will stimulate a debate between research and practice on suitable design and technology.
Keywords: Architecture; Business activity monitoring; Business process management; Business process re-engineering; Complex event processing; Computer software; Standard software

Non-perturbing cavitation detection / monitoring in sonochemical reactors - Bornmann, Peter; Hemsel, Tobias; Sextro, Walter; Maeda, Takafumi; Morita, Takeshi (Ultrasonics Symposium (IUS), 2012 IEEE International)
To optimize the ultrasound irradiation for cavitation based ultrasound applications like sonochemistry or ultrasound cleaning, the correlation between cavitation intensity and the resulting effect on the process is of interest. Furthermore, changing conditions like temperature and pressure result in varying acoustic properties of the liquid. That might necessitate an adaption of the ultrasound irradiation. To detect such changes during operation, process monitoring is desired. Labor intensive processes, that might be carried out for several hours, also require process monitoring to increase their reliability by detection of changes or malfunctions during operation. In some applications cavitation detection and monitoring can be achieved by the application of sensors in the sound field. Though the application of sensors is possible, this necessitates modifications on the system and the sensor might disturb the sound field. In other applications harsh, process conditions prohibit the application of sensors in the sound field. Therefore alternative techniques for cavitation detection and monitoring are desired. The applicability of an external microphone and a self-sensing ultrasound transducer for cavitation detection were experimentally investigated. Both methods were found to be suitable and easily applicable.
Keywords: cavitation; chemical reactors; microphones; process monitoring; reliability; ultrasonic applications; ultrasonic waves; acoustic properties; cavitation based ultrasound applications; cavitation intensity; change detection reliability; external microphone; malfunction detection reliability; nonperturbing cavitation detection; nonperturbing cavitation monitoring; process monitoring; self-sensing ultrasound transducer; sonochemical reactors; sonochemistry; ultrasound cleaning; ultrasound irradiation; Acoustics; Liquids; Monitoring; Sensors; Sonar equipment; Transducers; Ultrasonic imaging

A blueprint for event-driven business activity management - Janiesch, Christian; Matzner, Martin; Müller, Oliver (Lecture Notes in Computer Science)
Keywords: Reference architecture; business activity management; business process analytics; business process management; complex event processing

Simulating Tightly Intermeshing, Co-Rotating Twin Screw Extruders with SIGMA - Kretzschmar, Nils; Schöppner, Volker (Proceedings of the 2010 Summer Computer Simulation Conference)
A large proportion of plastics today is compounded, which means the process from refining a raw material to the processable material. For this process compounding extruders are used which mostly involve tightly intermeshing, co-rotating twin screw extruders. These extruders consist of two closely spaced screws which rotate in the same direction and convey the raw material to the screw tip. These screws are surrounded by several barrel modules which heat or cool the material. As the whole design of the machine is modularly arranged the process behavior of a twin screw extruder depends for the main part on the arrangement of the screw and the barrel elements. Until today this arrangement and process optimization is conducted by experienced engineers and with the help of trial-and-error methods. Furthermore, theoretical models are used with which the behavior of the extruder is estimated. As these models are mostly very complex they are only made available with the realization in different software projects. One of the tools is called SIGMA. Within this paper SIGMA is introduced as a software to optimize a twin screw extruder. SIGMA supports the engineer already in the early stages of the extruder arrangement.
Keywords: process optimization; polymer engineering; compounding; twin screw extruder; simulation

RTOS-Aware Refinement for TLM2.0-based HW/SW Design - Becker, Markus; Di Guglielmo, Giuseppe; Fummi, Franco; Müller, Wolfgang; Pravadelli, Graziano; Xie, Tao (Proceedings of DATE’10)
Refinement of untimed TLM models into a timed HW/SW platform is a step by step design process which is a trade-off between timing accuracy of the used models and correct estimation of the final timing performance. The use of an RTOS on the target platform is mandatory in the case real-time properties must be guaranteed. Thus, the question is when the RTOS must be introduced in this step by step refinement process. This paper proposes a four-level RTOS-aware refinement methodology that, starting from an untimed TLM SystemC description of the whole system, progressively introduce HW/SW partitioning, timing, device driver and RTOS functionalities, till to obtain an accurate model of the final platform, where SW tasks run upon an RTOS hosted by QEMU and HW components are modeled by cycle accurate TLM descriptions. Each refinement level allows the designer to estimate more and more accurate timing properties, thus anticipating design decisions without being constrained to leave timing analysis to the final step of the refinement. The effectiveness of the methodology has been evaluated in the design of two complex platforms.
Keywords: Timing; Hardware; Operating systems; Process design; Accuracy; Standards development; Context modeling; Real time systems; Communication channels; Microprogramming

The SATURN Approach to SysML-based HW/SW Codesign - Müller, Wolfgang; He, Da; Mischkalla, Fabian; Wegele, Arthur; Larkham, Adrian; Whiston, Paul; Penil, Pablo; Villar, Eugenio; Mitas, Nikolaos; Kritharidis, Dimitros; Azcarate, Florent; Carballeda, Manuel (Proceedings of the IEEE Computer Society Annual Symposium on VLSI)
The main obstacle for the wide acceptance of UML and SysML in the design of electronic systems is due to a major gap in the design flow between UML-based modeling and SystemC-based verification. To overcome this gap, we present an approach developed in the SATURN project which introduces UML profiles for the co-modeling of SystemC and C with code generation support in the context of the SysML tool suite ARTiSAN Studio®. We finally discuss the evaluation of the approach by two case studies.
Keywords: Communicate Sequential Process Virtual Platform Smart Camera Synchronous Data Flow Artisan Studio

Design and modeling of a domain ontology for fire protection - Pottebaum, Jens; Japs, Anna Maria; Prödel, Stephan; Koch, Rainer (ISCRAM 2010 -- 7th International Conference on Information Systems for Crisis Response and Management)
Keywords: Command and control process; Command and control systems; Design and modeling; Domain ontologies; Emergency response; Fire extinguishers; Fire protection; Heterogeneous domains; Information analysis; Information sharing; Information systems; Interoperability; Ontology language; Semantic technologies; Semantic Web; Semantics

Velocity Estimation of Mobile Terminals by Exploiting GSM Downlink Signalling - Peschke, Sven; Haeb-Umbach, Reinhold (4th Workshop on Positioning Navigation and Communication (WPNC 2007))
In this paper, we experimentally evaluate algorithms for velocity estimation of a GSM 900 mobile terminal which are based on the analysis of the statistical properties of the fast fading process. It is shown how theses statistics can be obtained from the training sequences present in downlink transmission bursts without establishing an active connection. Realistic simulations of a GSM channel according to the COST 207 channel models have been conducted. These models incorporate effects like multipath propagation, fading, cochannel interference and additive noise. It is shown that velocity estimation by searching for the maximum slope of the power density spectrum of the fast fading performs best.
Keywords: additive noise; cellular radio; channel estimation; cochannel interference; COST 207 channel models; downlink transmission bursts; fading channels; fading process; GSM downlink signalling; mobile terminals; multipath channels; multipath propagation; power density spectrum; statistical analysis; statistical properties; telecommunication links; telecommunication terminals; velocity estimation

Customer-Oriented Systems Design through Virtual Prototyps - Flake, Stephan; Geiger, Christian; Müller, Wolfgang; Ruf, Jürgen (Proceedings of IEEE KMN 2001)
Rapid prototyping based on 3D models is well accepted for several applications. This article addresses the application of animated virtual 3D prototypes for the development of computer-based systems supporting early collaboration of the system designer with the external customer. Our methodology seamlessly integrates illustration through 3D animation with the main tasks of computer-based real-time systems development, i.e., implementation and verification. The approach is outlined by the example of the design of a flexible manufacturing system.
Keywords: Virtual prototyping; Animation; Collaboration; System analysis and design; Feedback; Application software; Power system modeling; Handicapped aids; Process design; Contracts